Charter Schools, Race, and Urban Space: Where the Market Meets Grassroots Resistance by Kristen Buras - Polier, Nicole (Radical Teacher, 2016)
Review - Charter Schools, Race, and Urban Space: Where the Market Meets Grassroots Resistance by Kristen Buras, Reviewed by Nicole Polier.